[UF6]2−: A Molecular Hexafluorido Actinide(IV) Complex with Compensating Spin and Orbital Magnetic Moments. (7th August 2019) - Pedersen, Kasper S.; Meihaus, Katie R.; Rogalev, Andrei; Wilhelm, Fabrice; Aravena, Daniel; Amoza, Martín; Ruiz, Eliseo; Long, Jeffrey R.; Bendix, Jesper; Clérac, Rodolphe
Abstract: The first structurally characterized hexafluorido complex of a tetravalent actinide ion, the [UF6 ] 2− anion, is reported in the (NEt4 )2 [UF6 ]⋅2 H2 O salt (1 ). The weak magnetic response of 1 results from both U IV spin and orbital contributions, as established by combining X‐ray magnetic circular dichroism (XMCD) spectroscopy and bulk magnetization measurements. The spin and orbital moments are virtually identical in magnitude, but opposite in sign, resulting in an almost perfect cancellation, which is corroborated by ab initio calculations. This work constitutes the first experimental demonstration of a seemingly non‐magnetic molecular actinide complex carrying sizable spin and orbital magnetic moments. Abstract : Der elektronische Grundzustand des schwach magnetischen U IV wurde im Detail am simplen, strukturell charakterisierten [UF6 ] 2− ‐Anion mittels Röntgenabsorptionsspektroskopie, Magnetometrie und quantenchemischen Berechnungen untersucht. Die Zerlegung und Quantifizierung des relativ hohen Spins und Bahndrehimpulses liefern Schlüsselinformationen für ein besseres Verständnis der komplexen elektronischen Struktur von Actinoidionen.